2017
DOI: 10.1098/rsos.170654
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of water-stable copper-containing metal-organic frameworks

Abstract: Although metal-organic frameworks (MOFs) or porous coordination polymers have been widely studied, their antimicrobial activities have not yet been fully investigated. In this work, antifungal activity of copper-based benzene-tricarboxylate MOF (Cu-BTC MOF), which is water stable and industrially interesting, is investigated against Candida albicans, Aspergillus niger, Aspergillus oryzae and Fusarium oxysporum. The Cu-BTC MOF can effectively inhibit the growth rate of C. albicans and remarkably inhibit the spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 35 publications
6
41
0
Order By: Relevance
“…21 In contrast, it has been reported that microparticles of copper-containing metal-organic frameworks at concentrations as high as 0.5 mg mL À1 caused 50% of inhibition of F. oxysporum. 19 Summarizing, concentrations of the green-synthesized Cu-NPs higher than 0.75 mg mL À1 inhibit almost completely the growth of the three evaluated fungi with IRG near the 100%. As a sake of comparison, for the growth inhibition of F. solani, 1.2 mg mL À1 of chitosan NPs (size 200-433 nm) were needed.…”
Section: Antifungal Activitymentioning
confidence: 92%
See 3 more Smart Citations
“…21 In contrast, it has been reported that microparticles of copper-containing metal-organic frameworks at concentrations as high as 0.5 mg mL À1 caused 50% of inhibition of F. oxysporum. 19 Summarizing, concentrations of the green-synthesized Cu-NPs higher than 0.75 mg mL À1 inhibit almost completely the growth of the three evaluated fungi with IRG near the 100%. As a sake of comparison, for the growth inhibition of F. solani, 1.2 mg mL À1 of chitosan NPs (size 200-433 nm) were needed.…”
Section: Antifungal Activitymentioning
confidence: 92%
“…36 Similar effects have been reported for Cu-NPs used against Aspergillus niger, Aspergillus oryzae, and Fusarium oxysporum. 19 At a concentration of 0.25 mg mL À1 of Cu-NPs, F. solani and F. oxysporum clearly exhibit cell surface damage, such as loss of cell wall integrity and morphological changes that include inammation of cells ( Fig. 4c and 6c).…”
Section: Effect On the Fungal Morphologymentioning
confidence: 97%
See 2 more Smart Citations
“…14 MOF199, which is water-stable, has been proved to possess powerful antibacterial activity by inducing damage to the bacterial envelope. [15][16][17] Abbasi et al rst reported the antimicrobial activity of MOF199 coated on silk against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). 18 Further study by RodrÍguez et al found that a cellulose-MOF showed high antibacterial activity in both solid and liquid cultures, and copper ions did not leach from the coated fabric.…”
Section: Introductionmentioning
confidence: 99%